Cause-related marketing in international business: what works and what does not? - Vrontis, Demetris; Thrassou, Alkis; Christofi, Michael; Shams, S. M. Riad; Czinkota, Michael R. (My University, 2020)
Purpose: The purpose of this paper is to investigate the irrevocable role of cause-related marketing (CRM) and its research imperative, exploring its contemporary insights in and across international markets, toward scholarly and executive application. Design/methodology/approach: This research is theoretical and it compiles and interrelates, in a multiperspective fashion, significant extant works in the field; focusing on how established and emergent variables and constructs can be leveraged, in order to develop insights into what does and does not work in international CRM. Findings: Extant works on international CRM still present significant gaps pertaining to key questions. Furthermore, true understanding of CRM stems from comprehending consumers, both individually and collectively; and both their underlying and contextual motivators, factors and forces. This calls for a multiperspective and cross-disciplinary approach to CRM to that weaves in contextual (sociocultural, etc.) elements to the equation. Research limitations/implications: Limitations naturally pertain to the research's theoretical nature that requires empirical testing. Practical implications: CRM offers consumers both the means and the ends of acquiring their target core value benefits, additionally or peripherally to their core purchase purpose; potentially making the difference between business/brand success and failure. Social implications: Through CRM, the contemporary consumer seeks product value benefits that transcend quality and functionality (etc.), to engulf abstract and intangible values pertaining to social, ethical, self-image and self-actualization factors. Originality/value: The comprehensive review, contextual elucidations and cross-disciplinary perspectives of this paper originally present the scope, depth, complexity and gaps of the subject, and pave the way for the research that still needs to ensue.
Keywords: Cause-related marketing; Consumers; Insights; International marketing; Review; Value